Research methods in public administration and public management : an introduction - Thiel, Sandra van, 1968- (Routledge masters in public management, 2022)
"Research in public administration and public management has distinctive features that influence the choices and application of research methods. The standard methodologies for researching from the social sciences can be difficult to follow in the complex world of the public sector. In a dynamic political context, the focus lies on solving societal problems whilst also using methodological principles to do scientifically sound research. Research Methods in Public Administration and Public Management, Second Edition, represents a comprehensive guide to undertaking and using research in public management and administration. It is succinct but covers a wide variety of research strategies including action research, experiments, case studies, desk research, systematic literature reviews and more. It pays attention to issues of design, sampling, research ethics and data management. This textbook does explain the role of theory, but also offers many international examples and practical exercises. It takes us through the journey of research, starting with the problem definition, choice of theory, research design options and tools to achieve impactful research. New and revised material includes, but is not limited to: A closer look at popular methods like the experiment and the systematic literature review. A deeper examination of research ethics and data management. New examples from a wide range of countries. Updated 'Further Reading' material and additional useful websites. This exciting new edition will be core reading for students at all levels as well as practitioners who are carrying out research on public management and administration"--